Impact of Harvest Age on Corn (Zea Mays) Fodder Productivity - Ludfia Windyasmara; Engkus Ainul Yakin; Mustaqim, Fajar (Jurnal Biologi Tropis, 2024)
Corn fodder is simply seeding corn kernels that are sown until the age of 8-13 days. The harvest age of corn fodder is one way to regulate plant productivity factors. The regulation of the harvest age will affect regrowth, so it is very important to pay attention so that corn fodder plants can provide optimal production in both quantity and quality. The purpose of this study was to determine the effect of differences in harvest age on the productivity of corn (Zea mays) forage. This study used the Completely Randomized Design (CRD) method consisting of 4 treatments and 5 replications, namely T1 (harvest age 7 days), T2 (harvest age 14 days), T3 (harvest age 21 days) and T4 (harvest age 28 days). The parameters observed were plant height, number of leaves, wet biomass and dry biomass. The results showed that the average height of corn fodder plants (Zea mays) was T1; 1.11, T2; 4.96, T3; 8.30 and T4; 10. The average number of leaves of corn fodder plants (Zea mays) at T1; 0.34, T2; 1.30, T3; 1.30 and T4; 2.3. The average wet biomass of corn fodder plants (Zea mays) at T1; 197.67, T2; 249.33, T3; 246 and T4; 241.67. The average dry biomass of corn fodder plants (Zea mays) at T1; 35, T2; 47, T3; 45 and T4; 41. The conclusion of this study is that corn fodder with different harvest age variations has a very significant effect on plant height, number of leaves, wet biomass and dry biomass.